2020
DOI: 10.12806/v19/i4/t3
|View full text |Cite
|
Sign up to set email alerts
|

Elevating Leadership Development Practices to Meet Emerging Needs

Abstract: The changing landscape that leaders face demands an evolution of leadership development that not only builds skills but also grows a leader's capacity to effectively respond to and manage an ambiguous, uncertain and changing future. Based on adult development theory, we explore the nuanced difference of leadership development through two distinct, but equally useful lenses: horizontal and vertical leadership development.We examined the state of leadership development practice across fifteen large organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…During the coaching phases described by Kowalski (2020), questions accompanied by active listening demonstrated respect and sensitivity. Chesley et al (2020) described coaching using a vertical approach, with an emphasis on how coachees "understand and interact with the complexity of their environment" (p. 187) and on risk-taking. The study participants were able to strategize options and take risks through interactions with their coaches.…”
Section: Discussionmentioning
confidence: 99%
“…During the coaching phases described by Kowalski (2020), questions accompanied by active listening demonstrated respect and sensitivity. Chesley et al (2020) described coaching using a vertical approach, with an emphasis on how coachees "understand and interact with the complexity of their environment" (p. 187) and on risk-taking. The study participants were able to strategize options and take risks through interactions with their coaches.…”
Section: Discussionmentioning
confidence: 99%
“…These programs often create a hierarchy between expert and learner, frequently pro-mote traditional learning strategies, and utilize advisors and information delivery directed to or at the learner. 25 This method works well for programs whose goal is to develop theoretical knowledge, advance expertise, and teach factual content. This approach aligns with horizontal leadership development, that is, introducing new concepts and developing "hard skills," functional and technical competencies that lead to lateral growth within their current framework and perspectives, and is an important component of professional and leadership development.…”
Section: Coaching In Leadership Developmentmentioning
confidence: 99%
“…Conventional leadership development programs, such as mentoring, leadership training, and administrative fellowships—although perceived beneficial and helpful—frequently utilize traditional adult learning approaches and follow commonly used instructional models that rely heavily on lecture‐style delivery, small group discussion, and project‐based learning. These programs often create a hierarchy between expert and learner, frequently promote traditional learning strategies, and utilize advisors and information delivery directed to or at the learner 25 . This method works well for programs whose goal is to develop theoretical knowledge, advance expertise, and teach factual content.…”
Section: Coaching In Leadership Developmentmentioning
confidence: 99%
“…However, today's leaders also need highly developed cognitive, social and relational capabilities to lead through influence in rapidly changing, highly networked and collaborative environments (Day, 2000). To be successful, today's leaders require selfawareness and learning capabilities (Avolio & Hannah, 2008;Chesley, Egan, & Jones, 2019;Shavkun & Dybchinska, 2020), heightened social and emotional capacity (Day, 2000;Inglis & Steele, 2005), more complex ways of thinking (Brown, 2012;Inglis & Steele, 2005;Petrie, 2011), perspective-taking and self-reflection (Avolio & Hannah, 2008;Chesley et al, 2019;Jones et al, 2020) and the ability to work across boundaries (Chima & Gutman, 2020). Research has demonstrated that few leaders are successfully prepared with the development complexity needed to lead in today's VUCA world (Ghemawat, 2012;Kegan & Lahey, 2009;Leslie, 2015).…”
Section: Leadership Developmentmentioning
confidence: 99%
“…Unfortunately, the type of development leaders need is not easily obtained through shortskill development training programs (Allen & Wergin, 2009;Day, 2000). These horizontal leadership programs may be good at preparing leaders to succeed with well-defined tasks and outcomes (Chesley et al, 2019). However, they are not as effective when advancing a leader's ability to think and act in more strategic ways (Brown, 2012;Petrie, 2014).…”
Section: Leadership Developmentmentioning
confidence: 99%